Regularization methods for elliptic quasi-variational inequalities in Banach spaces. (2nd November 2021) - Su, Guangwang; Xue, Guangming; Xia, Guoen; Bin, Maojun
ABSTRACT: In this paper, we deal with a class of ill-posed quasi-variational inequalities with contaminated data by employing the elliptic regularization in Banach spaces. Firstly, we get an existence result for quasi-variational inequalities and show that the sequence of bounded regularized solutions converges strongly to a solution of the original quasi-variational inequalities under mild coercivity conditions. Next, we give the boundedness of regularized solutions for quasi-variational inequalities. Finally, an example is presented to illustrate our main results.